The potential of resistance inducers and synthetic fungicide combinations for management of foliar diseases of nursery stock. (July 2021) - Percival, Glynn C.; Graham, Sean
Abstract: Unmanaged, foliar diseases of nursery stock can be detrimental to woody plant biology and aesthetics. Build-up of disease resistance due to an over-reliance on synthetic fungicides means alternative disease management strategies are now recommended. The purpose of these studies was to investigate the effectiveness of three resistance inducers, harpin protein, salicylic acid derivative and chitosan that are commercially available to growers. Resistance inducers were applied alone and in combination with a synthetic fungicide (penconazole or boscalid + pyraclostrobin) against three foliar diseases ( Venturia inaequalis, Guignardia aesculi, Diplocarpon rosae ) using container grown stock. Nine experiments were conducted over five consecutive years. The use of a resistance inducer alone significantly reduced disease severity in six of the nine experiments. In eight of the nine experiments application of penconazole or boscalid + pyraclostrobin at 0.66 cc and 0.6 g l −1 i.e. two third manufacturers recommended rate in combination with a resistance inducer provided the same degree of disease control as penconazole or boscalid + pyraclostrobin applied at the manufacturers recommended rate of 1.0 cc and 0.9 g l −1 . Similarly, efficacy of a penconazole or boscalid + pyraclostrobin at 1.0 cc and 0.9 g l −1  + respectively + resistance inducer was greater than that of a penconazole or boscalid + pyraclostrobin at 1.0 cc and 0.9 g l −1 alone. Results conclude that combinations of a resistance inducer with a reduced dose of a synthetic fungicide are as effective as a fungicide applied at full strength, provided a minimum of four sprays are applied over a growing season, at reducing symptom severity of V. inaequalis, G.aesculi and, D. rosae . Highlights: Resistance inducers reduced severity of three foliar diseases. Resistance inducers plus a reduced fungicide dose effectively lower disease severity. Fungicide at full strength plus resistance inducer achieve maximum disease reductions. Resistance inducers offer potential to decrease fungicide selection pressure.